Public debate on research priorities - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
electronic conference held from 8 to 19 January 2001 by the NGO committee of the Consultative Group on International Agricultural Research (CGIAR) centres